2019
DOI: 10.1111/jam.14411
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of structural changes and intracellular substance leakage of Escherichia coli O157:H7 induced by ohmic heating

Abstract: Aims: To investigate the effects of ohmic heating (OH) and water bath heating (WB) on the membrane permeability, membrane structure, intracellular organization and leakage of intracellular substances of Escherichia coli O157:H7 at the same inactivation level and at a heating temperature of 72°C. Methods and Results: Flow cytometry analysis indicated that membrane permeability of E. coli O157:H7 by OH was comparable to WB at 72°C. Scanning electron microscopy analysis showed that the OH-treated E. coli O157:H7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Meanwhile, the protein concentration of the supernatant was measured by the BCA method. Absorbance values were determined at 450 nm using a microplate reader (Unico (Molecular Devices SpectraMax250, United States) ( Tian et al, 2019 ; Liao et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, the protein concentration of the supernatant was measured by the BCA method. Absorbance values were determined at 450 nm using a microplate reader (Unico (Molecular Devices SpectraMax250, United States) ( Tian et al, 2019 ; Liao et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Where CFU/mL CL was the counts on Compass Listeria Agar; CFU/ mL CLTSA was the counts on Compass Listeria Agar +TSA (22).…”
Section: Enumeration Of Viable and Injured Cellsmentioning
confidence: 99%
“…Many researchers have recently researched the use of ohmic heating to inactivate foodborne bacteria (13,18,22). Previous studies showed that OH is affected by extrinsic factors such as voltage and frequency and intrinsic factors such as features of lipids, proteins, carbohydrates and their quantities in food.…”
Section: Introductionmentioning
confidence: 99%
“…The practicality and cost-effectiveness of the OH system compared to other thermal heating methods have made it a promising application in the processing of dairy products (Bosi et al 2013). Although there are many studies on the application of OH in different food matrices (Park and Kang 2013, Cho et al 2017, Tian et al 2019, Pires et al 2020, Özkale and Kahraman 2023, research on pathogen inactivation in proteinenriched milks is quite limited as far as we know. This study aimed to investigate the effects of the OH process applied with different voltage gradients on L. monocytogenes inactivation and some quality parameters in protein-enriched milks.…”
Section: Introductionmentioning
confidence: 99%